A mathematical description accounting for the superfluous hydrogen evolution and the inductive behaviour observed during electrochemical measurements on magnesium. (1st June 2018) - Curioni, M.; Salamone, L.; Scenini, F.; Santamaria, M.; Di Natale, M.
Abstract: When electrochemical techniques are used to probe the surface of corroding magnesium with the aim of obtaining quantitative information on the corrosion process, two peculiarities are generally observed: i) with anodic polarization, the rate of hydrogen evolution increases instead of decreasing and ii) during electrochemical impedance spectroscopy measurements, an inductive contribution is often observed at the low-frequency end of the spectra. The presence of these two phenomena clearly has an impact on the methodology that should be applied to correctly estimate corrosion rates from electrochemical data. The aim of this work is to provide a general mathematical description of the corroding magnesium surface that, under minimal a priori assumptions regarding the reaction kinetics, can account simultaneously for both superfluous hydrogen evolution and inductive response. The mathematical results are consistent with the suggestion that the superfluous hydrogen evolution is mainly related to the increase of the surface of the active corrosion front during anodic polarization. Further, the obtained results show that the inductive response is expected when, at the corrosion front, oxidation of magnesium proceeds faster than hydrogen evolution. Graphical abstract: Image 1 Highlights: Mathematical description accounting for superfluous hydrogen evolution (SHE) and inductive behaviour (IB) for Mg. The results support that SHE relates to increase in area of the active corrosion front with anodic polarization. The results support that IB is due to rate of Mg oxidation being higher than hydrogen evolution at the corrosion front.